Regulation of Nicotine Tolerance by Quorum Sensing and High Efficiency of Quorum Quenching Under Nicotine Stress in Pseudomonas aeruginosa PAO1 - Tang, Huiming; Zhang, Yunyun; Ma, Yifan; Tang, Mengmeng; Shen, Dongsheng; Wang, Meizhen (Frontiers in Cellular and Infection Microbiology, 2018)
Quorum sensing (QS) regulates the behavior of bacterial populations and promotes their adaptation and survival under stress. As QS is responsible for the virulence of vast majority of bacteria, quorum quenching (QQ), the interruption of QS, has become an attractive therapeutic strategy. However, the role of QS in stress tolerance and the efficiency of QQ under stress in bacteria are seldom explored. In this study, we demonstrated that QS-regulated catalase (CAT) expression and biofilm formation help Pseudomonas aeruginosa PAO1 resist nicotine stress. CAT activity and biofilm formation in wild type (WT) and ΔrhlR strains are significantly higher than those in the ΔlasR strain. Supplementation of ΔlasI strain with 3OC12-HSL showed similar CAT activity and biofilm formation as those of the WT strain. LasIR circuit rather than RhlIR circuit is vital to nicotine tolerance. Acylase I significantly decreased the production of virulence factors, namely elastase, pyocyanin, and pyoverdine under nicotine stress compared to the levels observed in the absence of nicotine stress. Thus, QQ is more efficient under stress. To our knowledge, this is the first study to report that QS contributes to nicotine tolerance in P. aeruginosa. This work facilitates a better application of QQ for the treatment of bacterial infections, especially under stress.